EVALUATION OF SOME PERFORMANCE INDICATORS FOR THE TRACTOR (CASE JX75T) - Himoud, M. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The experiments were conducted on farm of the Agriculture College, University of Basrah, in a silty clay soil with moisture content of 16%. The tractor used in this research was (CASE JX75T) tractor for studying and evaluating its agricultural performance. The parameters of study include three level of tillage depths (10, 15 and 20 cm) and four forward speeds (G=1.9, G= 2.44, G3= 3.25 and G= 4.33 km/h) by using randomized complete block design (RCBD) with a split plots. The results showed that the increase in forward speed from (1.9 - 4.33km/hr) led to a significant increased in drawbar pull and wheel slippage by the following percentages (33.33%-15.78%).The obtained results for the range of tests showed that the maximum effective field capacity 2.52 donum/h was obtained at 4.33 km/h travelling speed, while the fuel consumption 7.9 l/hr, required power 29.66 kW, and specific energy 19 kw.hr/don. Respectively the traveling speed and soil moisture , ploughing depth , the most important factors that affecting the effective field capacity and drawbar pull, fuel consumption, specific energy.